Zoekend naar identiteit tussen taal en overtuiging: muziek en theater in Kortrijk tijdens de belle époque - Forment, Bruno 1978- (2023)
Around 1900, Kortrijk boasted a surprisingly vibrant musical life. Local choirs, brass bands, and symphonic ensembles performed in open-air kiosks and the municipal theatre. Their repertoires—ranging from Peter Benoit to Bizet—reflected a city navigating between Flemish cultural revival and French refinement. The annual travelling theatre fair drew large crowds, much to the dismay of Catholic and Flemish-nationalist circles, who fostered their own artistic platforms in groups like Vlaamsche Zonen. Around 1903, the city intervened: theatre became a public concern, culminating in the construction of a new City Theatre in neo-Flemish style. Music and theatre thus became not only artistic expressions but stages for ideological debate.
FRIS
Editorial review
Keywords: Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Theater history; Music history; Catholicism; Nationalism; Operetta; Opera